2006
DOI: 10.3748/wjg.v12.i48.7779
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Rockall scoring system for outcomes from non-variceal upper gastrointestinal bleeding in a Canadian setting

Abstract: AIM:To validate the Rockall scoring system for predicting outcomes of rebleeding, and the need for a surgical procedure and death. METHODS:We used data extracted from the Registry of Upper Gastrointestinal Bleeding and Endoscopy including information of 1869 patients with non-variceal upper gastrointestinal bleeding treated in Canadian hospitals. Risk scores were calculated and used to classify patients based on outcomes. For each outcome, we used χ 2 goodness-of-fit tests to assess the degree of calibration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 39 publications
3
43
0
3
Order By: Relevance
“…This is consistent with previously published data showing that the complete Rockall score is useful for the prediction of mortality but not for re-bleeding (14,15). Others have found the complete Rockall score to be predictive for re-bleeding and mortality (3) and to be able to identify a group of patients at low-risk for re-bleeding and mortality [Rockall score ≤ 2] (16).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with previously published data showing that the complete Rockall score is useful for the prediction of mortality but not for re-bleeding (14,15). Others have found the complete Rockall score to be predictive for re-bleeding and mortality (3) and to be able to identify a group of patients at low-risk for re-bleeding and mortality [Rockall score ≤ 2] (16).…”
Section: Discussionsupporting
confidence: 90%
“…Despite methodological and demographic differences, was closely correlated with the probability of death, but not so close to the chance of rebleeding [30][31][32]34,35] . This observation may be partly explained by the fact that the Rockall score was originally developed for the prediction of mortality rather than for the prediction of rebleeding and also because not all patients received endoscopic therapy [15] .…”
Section: The Importance Of Outcomesmentioning
confidence: 92%
“…In a prospective validation of this score, Rockall et al [28] showed that the patients with a score of 2 or less (29.4% of the cohort) had a rebleeding rate of 4.3% and a mortality rate of 0.1%, suggesting that such patients could have been safely managed in the outpatient setting. The Rockall score has been prospectively and externally validated in different populations [29][30][31][32] . Church and Palmer from Edinburgh proposed that the Rockall score could be used to predict rebleeding and death by doing a retrospective analysis of cases of peptic ulceration enrolled into two trials of endoscopic haemostasis.…”
Section: The Importance Of Outcomesmentioning
confidence: 99%
“…Hematemesis and melena, according to the previous study, were proved as an early manifestation of UGIB, both variceal and non-variceal, where approximately 30% of patients with bleeding ulcers begins with hematemesis, 20% with melena, and 50% both. (5,13) Patients with a history of UGIB is usually followed by a significant decrease in hemoglobin. This study indicated a significant difference between the increase in the mGBS and the decline in hemoglobin in patients with UGIB.…”
Section: Table 2 Independent T-tests Of Each Parameter Of Gbs and Thmentioning
confidence: 99%